SHC Task 48 B2 – Three GOOD Practice Examples of Solar Heat Driven Desiccant Evaporative Cooling Systems. (June 2016) - Selke, Tim; Frein, Antoine; Muscherà, Matteo; Sethuvenkatraman, Subbu; Hands, Stuart; White, Stephen
Abstract: Within the activity B2 of IEA SHC Task48, an exhaustive report on GOOD Practice examples of existing solar heat driven desiccant cooling (SDEC) systems was written. Three SDEC systems from Austria, Australia and Italy are well documented from the design phase to the operational phase. The authors of the GOOD Practice SDEC systems belong to research entities and the selected SDEC projects were scientifically accompanied by these partners from the very beginning on. The energy performance of all three SDEC systems in operation is indicated by monthly energy fluxes and key performance indicator as a result from measurement data of a scientific monitoring campaign. The GOOD Practice SDEC report on each system closes with findings and lessons learned in order to guide next projects by answering; What quality and support measures lead to a successful SDEC system implementation with high energy performance figures, high quality of indoor comfort and high user friendliness for facility manager? The SHC Task48 B2 report is published on the official SHC Task48 website.